Human Prostate Fibroblasts Induce Growth and Confer Castration Resistance and Metastatic Potential in LNCaP Cells - Thalmann, George N. (2009)
BACKGROUND: The tumor microenvironment is important for progressive and metastatic disease. OBJECTIVE: To study the hypothesis that prostate fibroblasts have differential ability to induce castration-resistant prostate cancer (PCa) and metastatic progression and whether this effect might vary depending on the zonal origin of the fibroblast. DESIGN, SETTING, AND PARTICIPANTS: Human prostate fibroblasts from the peripheral (PZ), transition (TZ) and central (CZ) zones of radical prostatectomy specimens (n = 13) were isolated and compared for their ability to promote androgen independence and metastatic progression in androgen-responsive PCa lymph node carcinoma of the prostate (LNCaP) cells in vivo. INTERVENTIONS: By coinoculating marginally tumorigenic LNCaP cells with PZ or TZ and by altering host hormonal milieu, a series of tumorigenic and metastatic LNCaP epithelial sublines–P4, P4-2 (derivatives from interaction with PZ), T4, and T4-2 (derivatives from interaction with TZ)–were established and characterized. MEASUREMENTS: In vivo and in vitro evaluation of induction of tumor growth and metastatic potential. RESULTS AND LIMITATIONS: 1) LNCaP sublines were permanently altered in their cytogenetic and biologic profiles after cellular interaction with prostate stromal fibroblasts. LNCaP sublines grew faster under anchorage-dependent and -independent conditions, expressed 1–12-fold more prostate-specific antigen in vitro than LNCaP cells, and gained metastatic potential; 2) zonal differences of stromal fibroblasts in their ability to induce the growth and progression of LNCaP tumors as xenografts in mice may exist but need further analysis; 3) PZ-conditioned medium induced more anchorage-independent growth of LNCaP cells in vitro. TZ had a higher growth rate and were more sensitive to dihydrotestosterone. CONCLUSIONS: We demonstrate that prostate fibroblasts have growth inductive potential on PCa cells and affect their subsequent progression to castration resistance and development of a metastatic phenotype.